INNOVATIVE PEDAGOGICAL TECHNOLOGIES FOR ENHANCING COGNITIVE ACTIVITY AND COMMUNICATIVE COMPETENCE OF PHYSICS STUDENTS IN PROFESSIONALLY ORIENTED ENGLISH LANGUAGE INSTRUCTION (Journal of Universal Science Research, 2025)
The article explores innovative pedagogical technologies aimed at developing cognitive activity and communicative competence of physics students in professionally oriented English language teaching. Particular attention is paid to Content and Language Integrated Learning (CLIL) and Project-Based Learning (PBL) as effective approaches that integrate subject content and foreign language learning. These methods promote active learning, critical thinking, and professional communication skills, preparing students for participation in the global scientific community.